Desarrollo de un detector juguete basado en el experimento CMS para la búsqueda de partículas neutras con largo tiempo de vida - Coll Saravia, Lucía Ximena (2020)
The Standard Model (SM) of particle physics consists in a description of all the known elemen-tary particles and their interactions. As far as it is known, the SM has passed all experimental tests, but presents some imperfections such as the presence of neutrino masses and the hierarchy problem. This encourages to probe theories beyond the Standard Model (BSM) that could bring solutions to these problems. An interesting proposal is to search for neutral long lived particles (LLP). These type of particles have long decay lengths and can be generated by a variety of BSM models such as Supersymmetry (SUSY), which proposes a solution to the hierarchy problem, and the Seesaw Mechanism that generates massive neutrinos. The detection of the decay products of LLPs would contribute to the discovery of new physics. The objective of this work is to develop a toy detector based on C++ and Pythia8 with the purpose of creating a tool for searches of neutral long lived particles. All the features, including the geometric characteristics and the particle accep- tance are constructed with information from the sub detectors of the CMS experiment. We use a Minimal SUSY process that violates R parity (RPVMSSM) to simulate processes producing LLPs in MadGraph5 and study the response of the toy detector. We conclude our simulation properly recreates important experimental conditions, and is suitable as a first step towards an international competitive particle physics tool.